Caregivers’ experiences: major challenges families’ face in caring for people with chronic illnesses in Ethiopia - Kaleab Fikre (Cogent Public Health)
Chronic illnesses have become a significant global health threat, particularly to families who often bear the caring burden. This article details the major challenges families experience in caring for people with chronic illnesses in Ethiopia. This qualitative study conducted 20 in-depth interviews with 10 different families recruited from Tikur Anbessa Specialized Hospital in Addis Ababa, who accompanied people with cancer, diabetes, and hypertension for medical appointments. It analyzed the collected data thematically. The findings revealed that families often bear the responsibility of caring for people with chronic illnesses, facing challenging situations. These challenges include a lack of knowledge about the illness, chaotic emotions intensified by the illness, and the trauma and unpredictability of the diseases. A lack of knowledge about the illness often leads to misunderstanding and strained relationships, hindering the ability to provide optimal care. Thus, caregivers experience chaotic emotions, such as shock, anxiety, fear, or sadness. Besides, external factors like work-related stress affect families dealing with chronic illnesses, resulting in sudden hospital stays, disruptions to daily routines, and unexpected financial strains. The study highlights that families often need to have a better understanding of the illnesses to be better equipped to deal with the challenges of chronic illnesses.